Barriers, knowledge, and training related to pharmacists' counselling on dietary and herbal supplements: a systematic review of qualitative studies - Jeremy Y. Ng; Umair Tahir; Simran Dhaliwal (BMC, 2021)
Abstract Background Pharmacists are recognized as one of the most accessible healthcare providers and are licensed to advise patients on drugs and health products including dietary and herbal supplements (DHSs). The objective of this study was to identify barriers, knowledge, and training that pharmacists report related to DHSs counselling. Methods MEDLINE, EMBASE, AMED and CINAHL were systematically searched from database inception to May 8th, 2020. Eligible articles contained qualitative data with a specific focus on pharmacists' perceived knowledge, training, and barriers to DHSs counselling. Relevant data were extracted, and a thematic analysis was conducted. Results Nineteen articles met the inclusion criteria. The following three main themes were identified: challenges to pharmacists obtaining DHSs education, postgraduate workplace challenges surrounding DHSs, and pharmacists' perceived role and importance on DHSs. Low knowledge of DHSs and the limited regulations surrounding DHSs acting as a barrier to counselling were common findings supported by the eligible articles. Conclusions A lack of pharmacists' knowledge and awareness of DHSs stems from a variety of factors including a lack of education and training in the field, limited regulations surrounding DHSs, and inadequate availability of DHS information resources in the pharmacy. Pharmacists were unable to confidently counsel patients due to these aforementioned factors in addition to reporting that they lacked time. Further research that reviews pharmacy education and workplace training, and improving DHS regulations are warranted future directions.